PENGEMBANGAN MEDIA KARTU BERGAMBAR PADA PELAJARAN IPA UNTUK MENGIDENTIFIKASI MAHLUK HIDUP - Widia Indah Rahayu; Ujang Jamaludin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The purpose of this study is to understand how the feasibility of media development picture CARDS on science lessons as the ability of students to identify living things. The type on this method is research and development.Data collection on this research is analysis and data collection used to see students' ability in science study, product design is used for student attractions in learning, media validation and testing validates by materials and education practitioners. After validating by teams of experts, after validation is done by material expert, media expert and educators response then a flash media card at the test at SDN Karawaci Baru 1 City of Tangerang Province of Banten with 32 students. According to assessments by materials received an 87% yield, a media expert's assessment is 88%, and an educator's response is 90%. Got the results of a